The acute toxicity of acetylcholinesterase reactivators in mice in relation to their structure - Bartosova, Lucie; Kuca, Kamil; Kunesova, Gabriela; Jun, Daniel (Neurotoxicity research, 2006)
Oximes in combination with atropine, are an integral part of the treatment of acute intoxications with organophosphorus insecticides or with the nerve agents such as tabun, sarin, soman, cyclosarin or VX. Organophosphorus compounds are extremely potent inhibitors of the enzyme acetylcholinesterase (AChE, 3.1.1.7). The pharmacological action of oximes is multiple: they are able to reactivate the inhibited AChE, but they affect acetylcholine release in peripheral and central cholinergic synapses, allosterically modulate the muscarinic receptors in peripheral and central synapses, and influence the nicotinic receptor-associated ion-channels. In our study, we have determined the acute toxicity of different structures of oximes after intramuscular application in mice. The acute toxicity of oximes is crucial for the assesment of a dose applied as a treatment for organophosphorus intoxications. We have tested 7 oximes of different structures (HS-6, K033, BI-6, MMB-4, K048, HI-6 and obidoxime ) and during our experiments we have observed the intoxication process including typical signs of intoxication, and times of death. K033 was the most toxic oxime with an LD50 of only 48 mg/kg, while the least toxic oxime - HI-6 - has an LD50 value of 671 mg/kg. All the oximes tested were of the bispyridinium type, with different length or shape of the connecting chain and positions of oxime groups at the pyridinium rings. All these structural features play an important role in biological activity of these compounds performed by their acute toxicity as well as by their reactivation potency.
Keywords: Animals; vztahy mezi strukturou a aktivitou; Acetylcholinesterase; Structure-Activity Relationship; Female; zvířata; Mice; acetylcholinesterasa; reaktivátory cholinesterasy; ženské pohlaví; Cholinesterase Reactivators; myši